2015
DOI: 10.1038/srep07783
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance of In2O3-based ceramics via Nanostructuring and Point Defect Engineering

Abstract: The issue of how to improve the thermoelectric figure of merit (ZT) in oxide semiconductors has been challenging for more than 20 years. In this work, we report an effective path to substantial reduction in thermal conductivity and increment in carrier concentration, and thus a remarkable enhancement in the ZT value is achieved. The ZT value of In2O3 system was enhanced 4-fold by nanostructuing (nano-grains and nano-inclusions) and point defect engineering. The introduction of point defects in In2O3 results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 31 publications
3
53
1
Order By: Relevance
“…The single element substitution of Co [6], Sn [7], and co-substitution of Zn+Nd [8], Zn+Ge [9], Zn+Ce [10], M+Sn (M=Zn, Cu, Ni) [11] for the indium site has been recently investigated and ZT values as high as 0.3 can be obtained at high temperatures. The approaches of fine-grained and high packing were also performed to decrease the thermal conductivity [12,13].…”
Section: T/ρκ Smentioning
confidence: 99%
“…The single element substitution of Co [6], Sn [7], and co-substitution of Zn+Nd [8], Zn+Ge [9], Zn+Ce [10], M+Sn (M=Zn, Cu, Ni) [11] for the indium site has been recently investigated and ZT values as high as 0.3 can be obtained at high temperatures. The approaches of fine-grained and high packing were also performed to decrease the thermal conductivity [12,13].…”
Section: T/ρκ Smentioning
confidence: 99%
“…[28,178] demonstrated that in nanostructured In 2 O 3 :MO x (M = Cr, Mn, Ni, Zn, Sn) ceramics, the thermal conductivity decreased to k~1.58-1.75 W/m·K at RT irrespective of the chemical nature of the second phase. Lan et al [166] reported on the thermal conductivity k~1.2 W/m·K at 973 K in sintered In 2 O 3 doped by Zn and Ce that is below the amorphous limit [142]. Approximately in the same range was the minimum thermal conductivity of In 2 O 3 doped with Ge [70].…”
Section: Thermal Conductivitymentioning
confidence: 89%
“…For In 1.92 (ZnCe) 0.08 O 3 this regularity is shown in Figure 8. The rapid decrease of thermal conductivity in comparison with bulk values takes place with the reduction of grain size [38,166,177]. For example, Ohtaki and co-workers.…”
Section: Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the mid-1900's, the thermoelectric properties of TiO 2 were being investigated with modification of extrinsic and intrinsic defect levels to alter the thermopower [15,130] Aside from point defect scattering, common strategies to reduce thermal conductivity for thermoelectrics lie in nano-structuring [49,117,118] and introduction of nano-particles [114,135]. Advances with respect to complex oxide thermoelectrics have been made in superlattice structures with interrupted interfaces [51] as well as incorporation of nano-scale grain boundaries and inclusions into already defected oxides [127].…”
Section: Functional Oxide Applications In Thermal Insulationmentioning
confidence: 99%